2008
DOI: 10.1002/gcc.20607
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time quantitative PCR analysis of pediatric ependymomas identifies novel candidate genes including TPR at 1q25 and CHIBBY at 22q12‐q13

Abstract: Loss of chromosome 22 and gain of 1q are the most frequent genomic aberrations in ependymomas, indicating that genes mapping to these regions are critical in their pathogenesis. Using real-time quantitative PCR, we measured relative copy numbers of 10 genes mapping to 22q12.3-q13.33 and 10 genes at 1q21-32 in a series of 47 pediatric intracranial ependymomas. Loss of one or more of the genes on 22 was detected in 81% of cases, with RAC2 and C22ORF2 at 22q12-q13.1 being deleted most frequently in 38% and 32% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 68 publications
(99 reference statements)
3
51
0
Order By: Relevance
“…Intracranial ependymomas have also demonstrated hypermethylation of the tumor suppressor gene HIC-1 (17p13.3) in 83% of cases, while such findings were not present in spinal cord ependymomas [4,59,60].…”
Section: Intracranial Tumorsmentioning
confidence: 93%
“…Intracranial ependymomas have also demonstrated hypermethylation of the tumor suppressor gene HIC-1 (17p13.3) in 83% of cases, while such findings were not present in spinal cord ependymomas [4,59,60].…”
Section: Intracranial Tumorsmentioning
confidence: 93%
“…Reduced expression of other genes within 22q13.1-13.33 has been observed, including CBX7, G22P1, and MCM5, which may be involved in gene silencing, DNA repair, and cell proliferation, respectively (77,148). Real-time quantitative PCR of 47 pediatric intracranial ependymomas revealed frequent loss of C22orf2 and RAC2, the latter being associated with reduced overall survival in the cohort (112).…”
Section: Immunohistochemical and Genomic Markersmentioning
confidence: 99%
“…These genes and the locus 1q25 merit further investigation with high resolution genomic techniques and gene expression studies that analyze larger numbers of pediatric ependymomas as an independent cohort. These methods could also establish the prognostic role of genes such as NRXN2, TPR, SEMA5, NRCAM, CDK4, and ADRM1 that have already been associated with outcome in small studies of pediatric patients with intracranial ependymoma (83,112), or examine other regions of genomic imbalance potentially harboring markers of disease progression and prognosis in children including the loss of chromosomes 22q and 6q.…”
Section: Immunohistochemical and Genomic Markersmentioning
confidence: 99%
“…24,25 It has been reported that Cby1 expression is significantly downregulated in chronic myeloid leukemia 26 and pediatric ependymomas. 27 To gain insights into the function of Cby1 in colorectal tumorigenesis, we created Cby1-knockdown (K D ) SW480 clones stably expressing Cby1 small-hairpin (sh) RNAs.…”
Section: Introductionmentioning
confidence: 99%